Sub-epithelial hyalinization, incomplete cystic lining, and corrugated surface could be a predictor of recurrence in Odontogenic Keratocysts - Dominic Augustine; Roopa S. Rao; Surendra Lakshminarayana; Kavitha Prasad; Shankargouda Patil (Elsevier, 2021)
Background: Odontogenic Keratocysts (OKCs) are known for their rapid growth and tendency to invade the adjacent tissues. Its high recurrence rate (2.5%-62%) has attracted many kinds of research to identify new parameters to predict recurrence that would enable better treatment outcomes for such patients. The present study aims to correlate Sub-Epithelial Hyalinization (SEH) that has not been explored in an Asian population to date and other histopathologic features of OKC to its recurrence propensity. Materials & Methods: A total of 60 OKCs were analyzed for histopathologic correlation of thickness of lining, complete/incomplete lining, corrugated surface, ortho/para keratinization, intercellular edema, reversed polarity, basilar hyperplasia, the palisading arrangement of basal cells, presence/absence of rete pegs, folding of the epithelium, epithelial/connective tissue separation, SEH, basal offshoots, daughter cysts and inflammation with recurrence to arrive at the most significant histologic feature predicting recurrence. Results: The most significant histologic parameter differentiating recurrent and non-recurrent OKCs was the presence of SEH (p = 0.004), incomplete lining epithelium (p ​= ​0.023), and a corrugated surface (p ​= ​0.049). Several other histologic parameters evaluated did not statistically correlate with recurrence, this can be attributed to the smaller sample size considered in the present study. Conclusion: SEH is a reliable histologic parameter to predict recurrence in OKCs. The presence of SEH is indicative of a higher recurrence potential in OKCs. Evaluation of histological parameters and their correlation with recurrence in OKCs on a larger sample size could validate the results of the current study undertaken and potentially unravel more insights on predicting recurrence. Key messages: Sub-epithelial hyalinization is a significant feature for predicting recurrence in OKC